Open Banking and Its Implications - WÓJCIK-CZERNIAWSKA Agnieszka; NOWAK Jacek (Communications of International Proceedings, 2022)
Open Banking is a progressive version for the monetary enterprise now no longer best from an opposition angle but additionally from a patron engagement angle. Banks will assist their clients with advanced and extra agile contributions. Banks need to permit their clients to manipulate their monetary affairs, make higher decisions, keep money, etc. Using API, banks can remodel their center structures for improvements and may combine with inner structures and outside companions in a humbler, stable, and managed way. In this paper, we are searching for to do things. Firstly, what’s open banking, and secondly through exploring the numerous programs of open banking stated with inside the extant literature, we articulate what are the applicable theories that supply upward thrust to the brand-new organizational systems and platform commercial enterprise fashions we take a look at with inside the virtual age. The financial sector will be shaken by open banking concepts in the same way that the insurance sector was shaken by price-comparison services. Customers are allowed to get charged of their funds, generally, improve choices, and handle various accounts all from one app.
Keywords: Open Banking; APIs; Consumers; Financial Services; Banks